A new strategy to achieve high antimicrobial activity: green synthesised silver nanoparticle formulations with Galium aparine and Helichrysum arenarium - Ozdemir, Cilem; Gencer, Merve; Coksu, Irem; Ozbek, Tulin; Derman, Serap (SCIENDO, 2023)
Silver nanoparticles (AgNPs), which have recently gained attention due to their antimicrobial activity, can also be produced by green synthesis. The aims of this study were to (i) characterise green synthesized AgNPs using microwave-assisted aqueous extracts of Galium aparine (G-AgNPs) and Helichrysum arenarium (H-AgNPs) and (ii) investigate the combined antimicrobial effects of the G- and H-AgNPs in different ratios. Nanoparticle formation and reactions were determined with UV-Vis spectroscopy. The G-AgNPs were 52.0 +/- 10.9 nm in size, with a 0.285 +/- 0.034 polydispersity index (PDI), and a -17.9 +/- 0.9 mV zeta potential. For H-AgNPs these characteristics were 23.9 +/- 1.0 nm, 0.280 +/- 0.032, and -21.3 +/- 2.7 mV, respectively. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) confirmed that the particles were monodisperse and spherical. The Fourier transform-infrared spectroscopy (FT-IR) results showed the presence of reducing agents that stabilised the AgNPs. Three different nanoformulations (NF-1, NF-2, and NF-3) were prepared by combining these two synthesised nanoparticles in different ratios and their antimicrobial activity was tested against E. coli, S. aureus, C. albicans, and A. flavus. Our study is the first to show that combining AgNPs from two different biological sources can produce effective nanoformulations with improved antibacterial activity against E. coli and S. aureus. These nanoformulations showed lower minimum inhibitory concentrations (31.25 mu g/mL against E. coli with all NFs; 62.5 mu g/mL for NF-1 and 125 mu g/mL for NF-2/3 against S. aureus) than G-AgNPs (62.5 mu g/mL for E. coli) or H-AgNPs (125 mu g/mL for S. aureus) alone. Their high combined inhibitory effect against E. coli (NF-1-3) was synergistic and against S. aureus (NF-2 and NF-3) potentially additive. Considering such promising results, we believe our study provides some direction for new research and strategies in antimicrobial therapeutics.
Keywords: A. flavus; antimicrobial nanosystems; C. albicans; E. coli; plant extracts; S. aureus; synergistic effect; ANTIBACTERIAL ACTIVITY; EXTRACT; ANTIOXIDANT; ACID; Public, Environmental & Occupational Health; Toxicology